2017
DOI: 10.1093/jee/tox249
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis to Determine the Half-life and Bioavailability of the Termiticides Bifenthrin and Fipronil in Soil

Abstract: The aim of this study was to test the bioavailability and degradation in soil of the termiticides bifenthrin and fipronil, which are used to treat subterranean termites (Heterotermes indicola, Wasmann). Soil collected from different areas of Lahore was categorized as sandy clay loam (SCL) or sandy loam (SL). Laboratory bioassays were conducted to determine the bioavailability ratio of bifenthrin and fipronil in each type of soil after different periods of time. LT50 values were determined posttreatment at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been reported that bifenthrin-exposure causes neurotoxic effects in mammals’ brains 3 , as well as apoptotic and inflammatory responses in murine brains 4 , 5 . Also, it was reported that bifenthrin is more hazardous than other SPs as it stays longer in the soil, quickly attaches to organic materials, and flows into aquatic areas, causing ecological dangers and harmful impacts on aquatic life 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that bifenthrin-exposure causes neurotoxic effects in mammals’ brains 3 , as well as apoptotic and inflammatory responses in murine brains 4 , 5 . Also, it was reported that bifenthrin is more hazardous than other SPs as it stays longer in the soil, quickly attaches to organic materials, and flows into aquatic areas, causing ecological dangers and harmful impacts on aquatic life 6 .…”
Section: Introductionmentioning
confidence: 99%
“…FMC Corporation, whose corporate headquarters are presently situated in Philadelphia, PA, was the first to produce bifenthrin. In Dec. 9, 1980 BF distinct from other synthetic pesticides, has a greater lethalness having negative impacts on aquatic organisms (Manzoor and Pervez, 2017). Bifenthrin is an insecticide used to restrict varied kinds of pests that harm to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BF exposure caused neurotoxic effects in mammals' brains as well as apoptotic and in ammatory responses in murine brains (Gargouri et al, 2018;Syed et al, 2018). It is more hazardous than other SPs because it stays longer in the soil, quickly attaches to organic materials, and ows into aquatic areas, causing ecological dangers and harmful impacts on aquatic life (Manzoor and Pervez, 2017). Because BF is used for pest control in agriculture and horticulture, there is de nitely a danger of long-term exposure to residues of pesticides in food products for humans (Pylak-Piwko and Nieradko-Iwanicka,…”
Section: Introductionmentioning
confidence: 99%